PENGARUH PUPUK KOTORAN BURUNG PUYUH DAN PUPUK NPK 16:16:16 TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) PADA MEDIA PMK DI PRE NURSERY - Aldi Ramadani; Raisa Baharuddin (DINAMIKA PERTANIAN, 2024)
This study aims to examine the combined effects of quail manure and NPK 16:16:16 fertilizer on the growth of oil palm seedlings (Elaeis guineensis Jacq.) in Red Yellow Podzolic soil during the pre-nursery stage. The research was conducted from February to May 2023 at the Experimental Farm of the Faculty of Agriculture, Riau Islamic University in Pekanbaru City. The experimental design utilized a Completely Randomized Design (CRD) with two factors. The first factor involved quail manure at four levels: 0, 200, 400, and 600 g per plant. The second factor consisted of four levels of NPK 16:16:16 dosage: 0, 15, 30, and 45 g per plant. Each treatment was replicated three times. The observed parameters included plant height, number of leaf midribs, stem diameter, wet weight, leaf length, and root length. Statistical analysis was performed, followed by the Honestly Significant Difference Test (BNJ) at a 5% significance level. The interaction between treatments significantly enhanced stem diameter (21.10 mm), plant wet weight (34.88 g), and root length (26.72 cm) with the combination of 600 g/plant quail manure and 45 g/plant of NPK 16:16:16 fertilizer. Quail manure had a significant main effect on all parameters, with the optimal treatment being 600 g/plant. Similarly, NPK 16:16:16 also had a significant main effect on all observed parameters, with the best treatment being 45 g/plant.